The Multiparty Trap in Indonesia's Presidential System: Between Democracy and Governmental Stability - Anwar Anwar; Muhammad Ramadhana Alfaris; Halimatus Khalidawati Salmah; Immanuel St Credo (Jurnal Hukum, 2026)
The relationship between Indonesia's post-amendment presidential system and its multiparty configuration remains a key constitutional issue, as political fragmentation often impacts executive stability, coalition formation, and government effectiveness. This study aims to analyze the constitutional position of Indonesia's presidential system, compare it with the United States model, and examine the implications of the Constitutional Court's ruling on party system regulation and effective governance. This study applies normative juridical methods using legal and conceptual approaches. The findings indicate that the post-amendment Constitution has strengthened presidentialism by affirming direct presidential elections, fixed terms, and removal only through constitutionally limited impeachment procedures. However, Indonesia's multiparty system requires the President to build parliamentary coalitions that can produce policy compromises, pragmatic bargaining, and unstable legislative support. Compared with the United States, Indonesia has a more flexible separation of powers, as the President is directly involved in lawmaking with the House of Representatives. The Constitutional Court's ruling opens new directions for evaluating presidential nomination thresholds and parliamentary thresholds in relation to representation and stability. The study finds that party simplification cannot be achieved simply by restricting political participation, as excessive restrictions can diminish democratic representation